Satellite-Driven Estimates of Water Mass Formation and Their Spatio-Temporal Evolution - Piracha, Aqeel; Sabia, Roberto; Klockmann, Marlene; Castaldo, Luigi; Fernández, Diego (Frontiers in Marine Science, 2019)
4 We derive water mass transformation and formation rates using satellite-derived datasets of 5 salinity, temperature and fluxes of heat and freshwater over the North Atlantic, North Pacific 6 and Southern Ocean. The formation rates are expressed in three coordinate systems: (1) density, 7 (2) temperature-salinity and (3) latitude-longitude. In the North Atlantic and North Pacific, peak 8 formation occurs south of the western boundary current extensions during the winter months of 9 the study period. In the Southern Ocean, wintertime peak formation occurs just north of the sub- 10 Antarctic Front. The satellite-derived water mass properties and formation areas agree well with 11 previous estimates from literature. The location of peak Mode Water formation varies slightly with 12 time in all coordinate systems. We assess seasonal and inter-annual variability in all three basins 13 from 2012 to 2014. We assess the impact of satellite uncertainties on final estimates of formation 14 rates and areas with Monte-Carlo simulations. The simulations provide insights on the associated 15 uncertainty of formation estimates. They also provide information on the geographic spread of the 16 water mass formation area subject to the satellite errors. We find that the total uncertainty is 17 dominated by the uncertainty in the sea surface salinity dataset. This stresses the need for frequent 18 and increasingly accurate sea surface salinity data for reliable estimates of water mass formation 19 rates and areas. Our study highlights the feasibility of providing satellite-based estimates of water 20 mass formation rates and areas. The good spatio-temporal coverage of satellite data further adds 21 to the utility of the approach.